Shoulder Rotational Properties of Throwing Athletes - Zheng, N.; Eaton, K. (International Journal of Sports Medicine, 2012)
Throwing arm injuries are common and often related to the shoulder external and internal rotation. Quantitative assessment may provide new insights to physical assessment and options for treatment. After having signed IRB approved consents and filled out injury questionnaires, 96 baseball pitchers were examined on both shoulders using a custom-made wireless device. The resistance onset angle (ROA), end-point angle (EPA), shoulder rotational flexibility (SRF) in both external and internal rotation, and rotational ranges of motion (ROM) of both shoulders were determined. About 34% of subjects had surgeries on their throwing arm. Another 15% of subjects had throwing arm injuries that did not require surgical treatments. The throwing arm had significantly lower internal ROA, EPA and SRF, but significantly higher external ROA, EPA and SRF than the non-throwing arm. There were significant differences in shoulder rotational properties among groups with different surgery locations. Subjects with shoulder surgeries had greater internal rotation flexibility of their throwing arm than those with surgeries on the elbow. Throwers with injury and surgery history had significantly different shoulder rotational properties. Abnormal shoulder rotational properties may be related to throwing arm injuries. A better understanding of their relationship may lead us to effective preventive measures of throwing arm injuries.
Keywords: throwing; injury history; rotational flexibility; range of motion; biomechanics